A comparison of the effect of the active release and muscle energy techniques on the latent trigger points of the upper trapezius. Issue 4 (October 2017) - Sadria, Golnaz; Hosseini, Majid; Rezasoltani, Asghar; Akbarzadeh Bagheban, Alireza; Davari, Ahmadreza; Seifolahi, Afsaneh
Abstract: Background/aim: The increasing use of computer in daily life has brought about numerous musculoskeletal problems. Impairments in the head, neck and shoulders are more common compared with the other parts of the body. The aim of this study was to compare the effect of two manual treatments in two separate groups, i.e., active release technique (ART) and muscle energy technique (MET) on the latent trigger points (LTrPs) in the upper trapezius muscle. The set criteria in the study included the active range of cervical lateral flexion, pain intensity on the visual analog scale (VAS), and the upper trapezius muscle thickness. Subjects and methods: This clinical trial study assessed the outcome measures within and between groups before and after the intervention. The target population were 64 (32 males, 32 females) participants who had been selected from among the staff members and the students of a rehabilitation school, and the employees of an engineering company who had LTrPs in their upper trapezius muscle and were from 18 to 50 years old. Results: The immediate effects of MET and ART on the patients of each groups with LTrPs in their upper trapezius muscle were increased active range of cervical lateral flexion (P < 0.001), decreased pain intensity on VAS (P < 0.05) and decreased thickness of the upper trapezius muscle (P < 0.01). Conclusion: Both manual techniques of ART and MET reduced the symptoms of LTrPs in the upper trapezius in the two groups equally, neither technique being superior to the other.